Using the RE‐AIM framework for dissemination and implementation of psychosocial distress screening. (10th April 2019) - Lazenby, Mark; Ercolano, Elizabeth; Tan, Hui; Ferrucci, Leah; Badger, Terry; Grant, Marcia; Jacobsen, Paul; McCorkle, Ruth
Abstract: Objective: To evaluate the RE‐AIM framework's effect on retention of participants and implementation outcomes of a 5‐year cancer research education programme on psychosocial distress screening in cancer centres across the United States. Methods: A one‐group pre‐/post‐test design was used to evaluate the programme on participant retention and implementation outcomes at 6, 12 and 24 months after enrolling in the programme (baseline) and analysed using descriptive statistics. Results: Seventy‐two cancer centres participated in four cohorts. Participant retention was 100%. At baseline and 24 months, respectively, 52 (72%) and 64 (88%) of the cancer centres had formulated a psychosocial distress screening policy; 51 (71%) and 70 (98%) had started screening in more than one clinic/population; 15 (21%) and 45 (63%) had started auditing health records for documentation of screening. Each outcome rate improved at the cancer‐centre level over the 24 months. Conclusion: RE‐AIM can be used as a framework for cancer research education programmes. Future research is needed on the use of a randomised adaptive design to test the optimal support for implementation of quality care standards according to cancer centres' needs.